Position Controller Design and Implementation of Ball and Beam System with SMC and PD Control Methods - Tayfun Abut (Energy Engineering and Control Systems)
Today, several methods are proposed and tested for controlling many nonlinear and unstable systems. This study employed the sliding mode control (SMC) and proportional-derivative (PD), which are used to control the position and modeling of ball and beam system that is a fundamental system used to test the control methods. Such systems are nonlinear and unstable due to their nature. Therefore, these systems are affected by external disturbances and this leads to a decrease in the control quality. The study tested the system by utilizing the classical PD and SMC methods, and the results were assessed by employing the Integral-Square-Error (ISE) performance criterion. The system results were provided as graphics and tables. Besides, the results were compared and analyzed.